2021
DOI: 10.3390/s21020562
|View full text |Cite
|
Sign up to set email alerts
|

Rotaphone-CY: The Newest Rotaphone Model Design and Preliminary Results from Performance Tests with Active Seismic Sources

Abstract: Rotaphone-CY is a six-component short-period seismograph that is capable of the co-located recording of three translational (ground velocity) components along three orthogonal axes and three rotational (rotation rate) components around the three axes in one device. It is a mechanical sensor system utilizing records from elemental sensors (geophones) arranged in parallel pairs to derive differential motions in the pairs. The pairs are attached to a rigid frame that is anchored to the ground. The model design, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Further, the recognition of rotations as an additional observable in seismology (W. H. K. Lee, 2009;Zembaty, 2009) is expected to result in significantly more recorded data in the near future. Recently many studies (Bernauer et al, 2020;Brokešová et al, 2021;Chiu et al, 2013;Igel et al, 2005Igel et al, , 2021 have reported the surface rotations measured due to earthquakes using improved instrumentation technology.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Further, the recognition of rotations as an additional observable in seismology (W. H. K. Lee, 2009;Zembaty, 2009) is expected to result in significantly more recorded data in the near future. Recently many studies (Bernauer et al, 2020;Brokešová et al, 2021;Chiu et al, 2013;Igel et al, 2005Igel et al, , 2021 have reported the surface rotations measured due to earthquakes using improved instrumentation technology.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…The first published results cannot be regarded as a fully satisfactory comparison of data from different sensors, as it can be concluded from the fundamental Bernauer et al paper [14]. However, the separate data from different kind of rotational devices, including Rothaphone-CY [15] or FOS5 [16], show a "light at the end of the tunnel" regarding future harmonization of data collected by such devices.…”
Section: Introductionmentioning
confidence: 99%
“…Bernauer et al [ 10 ] describe a field experiment, which took place in Fürstenfeldbruck in November 2019, that was devoted to the comparison of 24 rotation rate sensors under artificially induced seismic excitations. The other three papers are devoted to more detailed field tests of particular devices during the Fürstenfeldbruck experiment: Kurzych et al [ 11 ], Izgi et al [ 12 ], and Brokešová et al [ 13 ]. The paper by Cao et al [ 5 ] focuses on the performance characteristics of specific seismic rotational motion sensors.…”
mentioning
confidence: 99%